2011
DOI: 10.4314/evj.v15i1.67681
|View full text |Cite
|
Sign up to set email alerts
|

Bovine cysticercosis in Ethiopia: A review

Abstract: Bovine cysticercosis is an infection of cattle caused by Cysticercus bovis, the larval stage of Taenia saginata. It is an infection of public health significance as eating of raw or undercooked beef results taeniasis in human population and an important cause of economic loss mainly due to condemnation, refrigeration and downgrading of infected carcasses. Bovine cysticercosis is prevalent in cattle population of various regions of Ethiopia in a range of 2.2% to 26.25%. The reported rates of prevalence may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…The probable reason for the high burden of helminthiasis cases in the study districts could be associated with poor socio-economic status and poor environmental sanitation [32]. In addition, the consumption of raw animal meat could contribute to the high incidence of helminthiasis [33]. The highest incidence of helminthiasis cases in males above 15 years old during the summer (rainy) season could be associated with intensive engagement in farming activity, and availability of warmth and moisture environment that enhance the development of free-living infective stages of helminth parasites [34].…”
Section: Discussionmentioning
confidence: 99%
“…The probable reason for the high burden of helminthiasis cases in the study districts could be associated with poor socio-economic status and poor environmental sanitation [32]. In addition, the consumption of raw animal meat could contribute to the high incidence of helminthiasis [33]. The highest incidence of helminthiasis cases in males above 15 years old during the summer (rainy) season could be associated with intensive engagement in farming activity, and availability of warmth and moisture environment that enhance the development of free-living infective stages of helminth parasites [34].…”
Section: Discussionmentioning
confidence: 99%
“…They are frequently reported from different corners of the country [27][28][29], and the disease is much more common in rural areas of Ethiopia where dogs and domestic animals live in a very close association [30]. Additionally, where home slaughtering of cattle, sheep, goats and camels is still predominant and uncooked offal and carcass wastes are normally given for dogs and cats, peoples to eat the ingestion of raw or undercooked beef dishes such as ''kurt'' and ''kitfo'' [31][32][33]. However, there is lack of recent information on some major metacestodes in East Shoa Zone of Oromia Regional State particularly in and around Bishoftu.…”
Section: Journal Of Dairy and Veterinary Sciencesmentioning
confidence: 99%
“…Such differences in prevalence may be associated with the number of cattle examined, the sensitivity of the meat inspection procedures, which can be affected by the site and method of incision, abattoir facilities and management, the motivation and competency of the meat inspectors and the willingness of the owner to cooperate [11,15]. The geographical differences in the habit of raw meat consumption, environmental and personal hygiene, animal husbandry practices, proximity to waste water and accessibility of taenicides for treating animals might also contribute to differences in prevalence [15][16][17]. In this study it is found that sex and age has no association (p>0.05) with C. bovis prevalence in the selected cattle, it revealed that no significant risk factor for the infection of bovine cysticercosis among the animal slaughtered at Jijiga municipal abattoir.…”
Section: Discussionmentioning
confidence: 99%